Influence of Personality and Motivation on Oral Presentation Performance - Liang, Hsin-Yi; Kelsen, Brent (Journal of psycholinguistic research, 2018)
Personality and motivation have been identified as influential variables associated with foreign language learning; however, few studies have investigated their effect on oral presentations. This study addresses the importance of both personality and motivation in students’ collaborative oral presentation performance. A Big Five personality trait questionnaire measuring Extraversion, Agreeableness, Conscientiousness, Neuroticism and Openness to Experience, together with the Collaborative Inquiry-based Project Questionnaire measuring Task, Project Work, Reinforcement, Social Learning and Social Pressure motivational constructs were employed to evaluate 257 university students. In general, the results showed that Extraversion, Project Work and Social Pressure were significant correlates of oral presentation scores. The first result suggests that extraverts possess superiority in situations where oral language production is central to communication. This was particularly true for lower-level students, inferring that extraverted personalities can compensate for a lower English language ability. The second indicates that the inquiry-based nature of the assignments was an intrinsic motivator especially valued by extraverts. The third implies that extrinsic motivation was a factor influencing student performance. These findings extend previous research by highlighting the contextual relationships between these affective variables and performance in collaborative oral presentation contexts.